Crystal structure and phase transition of TlReO4: a combined experimental and theoretical study. (6th November 2020) - Mondal, S; Vaitheeswaran, G; Kennedy, Brendan J; Chay, Clarissa; Injac, Sean; Errandonea, Daniel
Abstract: The present work describes a density-functional theory (DFT) study of TlReO4 in combination with powder x-ray diffraction experiments as a function of temperature and Raman measurements at ambient temperature. X-ray diffraction measurements reveal three different structures as a function of temperature. A monoclinic structure (space group P 21 / c ) is observed at room temperature while two isostructural tetragonal structures (space group I 41 / a ) are found at low- and high-temperature. In order to complement the experimental results first-principles DFT calculations were performed to compute the structural energy differences. From the total energies it is evident that the monoclinic structure has the lowest total energy when compared to the orthorhombic structure, which was originally proposed to be the structure at room temperature, which agrees with our experiments. The structural and vibrational properties of the low- and room-temperature phase of TlReO4 have been calculated using DFT. Inclusion of van der Waals correction to the standard DFT exchange correlation functional is found to improve the agreement with the observed structural and vibrational properties. The Born effective charge of these phases has also been studied which shows a combination of ionic and covalent nature, resembling metavalent bonding. Calculations of zone-center phonon frequencies lead to the symmetry assignment of previously reported low-temperature Raman modes. We have determined the frequencies of the eight infrared-active, 13 Raman-active and three silent modes of low-temperature TlReO4 along with 105 infrared-active and 108 Raman-active modes for room-temperature TlReO4 . Phonons of these two phases of TlReO4 are mainly divided into three regions which are below 150 cm −1 due to vibration of whole crystal, 250 to 400 cm −1 due to wagging, scissoring, rocking and twisting and above 900 cm −1 due to stretching in ReO4 tetrahedron. The strongest infrared peak is associated to the internal asymmetric stretching of ReO4 whereas the strongest Raman peak is associated to the internal symmetric stretching of ReO4 . We have also measured the room-temperature Raman spectra of monoclinic TlReO4 identifying up to 28 modes. This Raman spectrum has been interpreted by comparison with the previously reported Raman frequencies of the low-temperature phase and our calculated Raman frequencies of low- and room-temperature phases of TlReO4 .